Keefektifan Metode Practice Rehearsal Pairs dan Media Animasi Powtoon Pada Keterampilan Bercerita (The Effectiveness of the Practice Rehearsal Pairs Method and Powtoon Animation Media on Storytelling Skills) - Arya Aqshal Prasetya; Rusnilawati Rusnilawati (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to examine the effectiveness of the practice rehearsal pairs method and Powtoon animation on storytelling skills. This quasi-experimental research has control and experimental classes. The experimental group received treatment in the form of a practice rehearsal pairs method with Powtoon media and the control group received treatment with a storytelling model with picture media. Both get pretest and posttest for. The prerequisite test uses SPSS 26. The result is a Sig. (2-tailed) 0.0000 <0.005 indicates that Ho is rejected. Storytelling skills in learning Indonesian for the two classes are slightly different. The experimental class pretest mean was 59.75 while the posttest was 82.25. The mean of the control class pretest was 57.50 while the posttest was 75.00. There are differences in the results of the experimental and control classes. The class that was given the treatment had higher results compared to the class that was not given the treatment.Penelitian ini bertujuan untuk menguji keefektifan metode practice rehearsal pairs dan animasi Powtoon pada keterampilan bercerita. Penelitian quasi experiment ini memiliki kelas kontrol dan eksperimen. Kelompok eksperimen mendapatkan perlakuan berupa metode practice rehearsal pairs dengan media Powtoon dan kelompok kontrol mendapatkan perlakuan dengan model story telling dengan media gambar. Keduanya mendapatkan pretes dan postes untuk. Uji prasyarat menggunakan SPSS 26. Hasilnya Diperoleh nilai Sig. (2-tailed) 0,0000 < 0,005 menunjukkan bahwa Ho ditolak. Keterampilan bercerita dalam pembelajaran Bahasa Indonesia terhadap kedua kelas sedikit berbeda. Rerata pretes kelas eksperimen adalah 59,75 sedangkan postes 82,25. Rerata pretes kelas kontrol 57,50 sedangkan postes 75,00. Ada perbedaan hasil dari kelas eksperimen dan kontrol. Kelas yang diberi perlakuan, hasilnya lebih tinggi dibandingkan dengan kelas yang tidak diberi perlakuan.